Design and crosstalk analysis of FBG-based optical add/drop multiplexers and optical crossconnects - Yuan, Hai. (2008)
Optical add/drop multiplexers (OADMs) and optical crossconnects (OXCs) are the most important network elements for optical wavelength division multiplexed (WDM) networks. They play important roles in enabling switching and routing capability with enhanced flexibility, survivability and efficient bandwidth management in WDM networks. Among all the optical components which can be used to construct OADMs and OXCs, fiber Bragg grating (FBG) is one of the most attractive components, because of its all ¬fiber geometry, low insertion loss, polarization insensitivity, longevity and ease of manufacturing. Hence, OADMs and OXCs based on FBGs are expected to achieve high performance with low implementation cost.